Locating narrow bipolar events with single-station measurement of low-frequency magnetic fields. (June 2016) - Zhang, Hongbo; Lu, Gaopeng; Qie, Xiushu; Jiang, Rubin; Fan, Yanfeng; Tian, Ye; Sun, Zhuling; Liu, Mingyuan; Wang, Zhichao; Liu, Dongxia; Feng, Guili
Abstract: We developed a method to locate the narrow bipolar events (NBEs) based on the single-station measurement of low-frequency (LF, 40–500 kHz) magnetic fields. The direction finding of a two-axis magnetic sensor provides the azimuth of NBEs relative to the measurement site; the ionospheric reflection pairs in the lightning sferics are used to determine the range and height. We applied this method to determine the three-dimensional (3D) locations of 1475 NBEs with magnetic signals recorded during the SHandong Artificially Triggered Lightning Experiment (SHATLE) in summer of 2013. The NBE detections are evaluated on a storm basis by comparing with radar observations of reflectivity and lightning data from the World Wide Lightning Location Network (WWLLN) for two mesoscale convective systems (MCSs) of different sizes. As revealed by previous studies, NBEs are predominately produced in the convective regions with relatively strong radar echo (with composite reflectivity ≥30 dBZ), although not all the convections with high reflectivity and active lightning production are in favor of NBE production. The NBEs located by the single-station magnetic method also exhibit the distinct segregation in altitude for positive and negative NBEs, namely positive NBEs are mainly produced between 7 km and 15 km, while negative NBEs are predominantly produced above 14 km. In summary, the results of comparison generally show that the single-station magnetic method can locate NBEs with good reliability, although the accuracy of 3D location remains to be evaluated with the traditional multi-station method based on the time-of-arrival technique. This method can be applied to track the motion of storm convection within 800 km, especially when they move out to ocean beyond the detection range (typically <400 km) of meteorological radars, making it possible to study NBEs in oceanic thunderstorms for which the location with multiple ground-based stations is usually not feasible. Highlights: Compact single-station method capable of getting 3D location of narrow bipolar events. Significantly larger detection range for strong echo than meteorological radars. Segregation of positive and negative NBEs in altitude for a broad area in East China.